Ultralight covalently interconnected silicon carbide aerofoam for high performance thermally conductive epoxy composites. (November 2020) - Vu, Minh Canh; Thieu, Nhat Anh Thi; Choi, Won Kook; Islam, Md Akhtarul; Kim, Sung-Ryong
Abstract: With the development of highly integrated electronic devices, there are growing demands for high performance thermal management materials with high thermal conductivity and electrical insulation. Herein, we report thermal properties of epoxy-based SiC aerofoam composites. A novel three-dimensional structure of covalently interconnected porous SiC (3D-SiC) aerofoam is successfully fabricated using 3D reduced graphene oxide foam as a template, and it was embedded in epoxy resin and cured to prepare thermoconductive composites. The formation of covalent SiC linkage and presence of interconnected 3D-SiC aerofoam resulted in thermal conductivity of the epoxy composites as high as 10.26 W·m −1 ·K −1 at 6.52 vol% of SiC, which calculated as thermal conductivity enhancement efficiency per 1 vol% of filler loading equals to 859%. The 3D-SiC/epoxy composites showed an excellent heat dissipation performance compared to that of a commercial thermal pad. The 3D-SiC/epoxy composite is a highly prospective candidate as next generation thermal dissipating material for electronic devices.